Denitrification Performance in Packed-Bed Reactors Using Novel Carbon-Sulfur-Based Composite Filters for Treatment of Synthetic Wastewater and Anaerobic Ammonia Oxidation Effluent - Wang, Yao; Liang, Baorui; Kang, Fei; Wang, Youzhao; Yuan, Zhihong; Lyu, Zhenning; Zhu, Tong; Zhang, Zhijun (Frontiers in Microbiology, 2022)
To avoid nitrate pollution in water bodies, two low-cost and abundant natural organic carbon sources were added to make up the solid-phase denitrification filters. This study compared four types of solid-phase carbon-sulfur-based composite filters, and their denitrification abilities were investigated in laboratory-scale bioreactors. The filter F4 (mixture of elemental sulfur powder, shell powder, and peanut hull powder with a mass ratio of 6:2.5:1.5) could achieve an optimal nitrate removal rate (NRR) of 723 ± 14.2 mg NO3–-N·L-1·d-1 when the hydraulic retention time (HRT) was 1 h, with the highest denitrification ability. Changes in influent pH largely impacted denitrification, and the content of shell powder has been proved to be an important part of the filter to alleviate water acidification. The HRT considerably impacted effluent quality after coupling of anaerobic ammonium oxidation (ANAMMOX) and solid-phase based mixotrophic denitrification process (SMDP). The concentration of suspended solids (SS) of the ANAMMOX effluent may present a risk in the coupling system. Autotrophs and heterotrophs were abundant and co-existed in all reactors; over time, the abundance of heterotrophs decreased while that of autotrophs increased. Overall, the findings of this study facilitate the development of technologies to further remove nitrogen from nitrogen-contaminated wastewater.